'Ghosts of Songs': The Haunting Soundtracks of the Black Audio Film Collective. Issue 2 (September 2015) - Smith, Kate Bolgar
<x content-type="archive" xml:space="preserve">Abstract</x> Throughout its existence as an innovative and influential collective of artists, the Black Audio Film Collective (BAFC) produced a number of films that are consistently concerned with archival images and sounds. Seen (and heard) from the perspective of this black British collective, the archive is understood not only to reveal an official memory of the past but also to signal the absence of certain narratives. BAFC's works interrogate these gaps in the archives, finding within them narratives and moments that speak of the black British experience. Reworking the archive in particular through their thoughtful and provocative soundtracks, BAFC present new ways of seeing and hearing the past, and new ways of conceiving of the present. Focusing on their most famous work Handsworth Songs (1986), this paper examines how the soundtracks resound with and against the archival images seen on screen. BAFC sample and distort voices and songs from the past, dubbing, versioning, and remixing them with discordant, unexpected sounds such as industrial noise and whale song. These splintered and haunting soundtracks open up the images to reinterpretation. Ultimately, this paper suggests that in a diasporic life characterised, as Derek Walcott describes it, by an 'absence of ruins', music and the collective memories heard within it can be considered as alternative archives: the intangibles of sounds and words acting in part as monuments to a history that is not registered in official books or buildings.